Citra Geisha dalam Masyarakat Jepang Tahun 1941 - 1956 - Putri, Indrany Yulian (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2021)
This articleÂ is called â€œGeishaâ€™s Images in Japanese Culture (1941Â â€“ 1956)â€. The reason why the writer wants to learn about Geisha is because Geisha is considered as a dirty job in Japan. The main problem that the writer studies is about the changing of Geishaâ€™s image between 1941 â€“ 1989. The methods that the writer uses is Historic Methods (Heuristic, Sources Critical, Interpretation and Historiography).Â Based on the research, the fact of Geisha Culture showed up in shogunat Tokugawa period. In the World War II, the Geisha Culture was disadvantaged by situation. In the end of the war, and The American Soldier lost war by Japan, Geisha Culture almost disappear. They considered Geisha Culture as a Yujo or known as prostitution.Through a lot of ups and down, Geisha gains their beauty images and trust as Japanese culture in a positive way. Until now, Geisha is known as the one and only Japanese culture genuinely.